Your period and your pregnancy, a cohort study of pregnant patients investigating the associations between menstruation and birth outcomes in Australia: study protocol - Miranda Davies-Tuck; Billie Bradford; Adrienne Gordon; Beverley Vollenhoven; Kirsten Rebecca Palmer; Kirstin Tindal; Caroline E Gargett; Fiona Cousins; Stacey Ellery (BMJ Open)
Introduction Early pregnancy care involves the screening and identification of women with risk factors for adverse pregnancy outcomes, including stillbirth or preterm birth, to tailor pregnancy care and interventions accordingly. Most stillbirths and approximately two-thirds of preterm births, however, occur in the absence of evident risk factors. The majority of stillbirths occur in the preterm period, yet there are few interventions targeting this period, and progress to reduce stillbirth rates remains slow. Placental dysfunction is a major contributor to stillbirth, particularly, preterm stillbirth. Here, the endometrial environment may shed light on factors that influence placental development and the trajectory of a pregnancy. Menstrual symptoms or abnormal uterine bleeding (AUB) can indicate endometrial disorders, which are associated with infertility and adverse pregnancy outcomes. Whether AUB is associated with pregnancy outcomes in the absence of a diagnosed endometrial pathology, however, remains unknown. Limited information regarding a woman’s menstrual cycle is captured in routine early pregnancy assessments, such as the last menstrual period and menstrual cycle length. Given the latent diagnosis of endometrial disorders and that up to a third of all women experience AUB during their lifetime, determining the association between menstrual characteristics and pregnancy outcomes has the potential to uncover new clinical strategies to reduce adverse pregnancy outcomes. Therefore, this study aims to understand the association between menstruation and pregnancy outcomes to identify which menstrual characteristics could provide value as a pregnancy risk assessment tool.Methods and analysis This is a prospective study of women aged 18–45 with a singleton pregnancy. Participants will be recruited in early pregnancy at their antenatal appointment and not have a known diagnosed endometrial pathology (endometriosis, adenomyosis, endometrial cancer or an endometrial submucosal fibroid) or have had an endometrial ablation. Participants will also be excluded if there is a planned termination of pregnancy or a termination of pregnancy for psychosocial reasons. Women will complete a menstrual history survey to capture menstrual cycle length, regularity, level of pain, heaviness of flow and other menstrual symptoms. Participants will consent to having the survey data linked with their pregnancy and birth outcome information. The primary outcome is a composite of stillbirth, spontaneous preterm birth, pre-eclampsia or fetal growth restriction. Participants will also be invited to complete an optional fetal movements survey at 28–32 and 36+ weeks’ gestation, and consent for placental collection at the time of birth will be sought.Ethics and dissemination Ethics approval was obtained from Monash Health Human Research Ethics Committee (83559) on 24 April 2024. The study will be conducted in accordance with these conditions. Findings will be disseminated through peer-reviewed publications and conference presentations.